Outbreak of nodular gill disease in farmed brook trout (Salvelinus fontinalis) - PEROLO A.; MANFRIN A.; DALLA POZZA M.; PRETTO T.; FIORAVANTI M. L.; GUSTINELLI A.; QUAGLIO F. (EAFP, 2019)
Introduction: Nodular gill disease (NGD) caused by amoebic infection represents an emerging and significant pathological condition associated with extensive mortality affecting freshwater reared salmonids, mainly rainbow trout (Oncorhynchus mykiss). Outbreaks of NGD have been reported in arctic char (Salvelinus alpinus), Chinook salmon (Oncorhynchus tshawytscha) and brown trout (Salmo trutta). In December 2017 the first case of NGD in farmed brook trout (Salvelinus fontinalis) associated with mortalities was observed during epidemiological amoe- bic investigations. Methodology: The disease occurred in a Northern Italy commercial rainbow trout culture facil- ity where periodic NGD’s episodes happened. The brook trout were imported from a Danish farm in November 2017 and allocated in a raceway supplied by river water with at 9 °C. The live weight was between 210 and 240 g. In the following month the fish showed signs of respiratory distress. The cumulative mortality, monitored from December 2017 to January 2018, reached 30%. Twenty fish from the investigated raceway were collected for necropsy, microscopical and parasitological analysis. Gills were dissected and fixed in 10% neutral buffered formalin solution for histological examination. The samples were dehydrated, embedded in paraffin, sectioned (4 μm) and stained with haematoxylin-eosin and Giemsa solution. Results and Conclusion: The samples did not showed noticeable macroscopical lesions with the exceptions of the gills, which appeared pale and swollen with whitish nodules located espe- cially in the distal part of the filaments. The microscopic examination of gill tissue revealed severe proliferative reaction with presence of amoebic organisms. The histology showed multi-focal epithelial hyperplasia of the gills causing lamellar fusion, cellular exfoliations, necrosis and amoebae (approximately 10×20 μm) along the surface of the affected filaments. In 9 out of 20 examined fish a massive presence of filamentous bacteria (referable to the family ...